Social resilience: goals and objectives for engaging urban design - Ragoschke, Adam S. (Kansas State University, 2014)
As the world continues to grow and cities continue to change, landscapes architects are constantly challenged with identifying design solutions that address the endless change of urban environments. In 1973, C.S. Holling developed the term “resilience theory,” which identified how social and ecological systems communicate across different landscape scales (Holling, C.S. 1973). In 2013, Kansas State Graduate Kevin Cunningham tested the validity of Holling’s resilience theory as a theoretical basis for urban design. This report attempts to further test the validity of resilience theory as a theoretical basis for social systems within urban design. Methodology utilized includes literature review with specific attention to current social resilience frameworks and guidelines, case study analyses, and an application of the author’s social resilience goals and strategies through a projective design of Washington Square Park, Kansas City, Missouri. Social resilience goals and strategies were developed to respond to social objectives identified within Washington Square Park RFQ/P, GDAP, Main Street Streetcar, Making Grand “Grand” and KCDC’s plan for the park. Objectives were derived based upon their relationship to resilience theory. The created social resilient goals, objectives and strategies will be specific for the revitalization of Washington Square Park. However, the process of identified social resilience goals, objectives and strategies can be utilized as a tool for designs of other urban, civic spaces. The process of identifying social resilience goals, objectives and strategies utilized within this report has the potential to continually promote landscape architects as the primary leaders in urban design practice.
Keywords: social; resilience theory; urban design; Landscape Architecture (0390); Land Use Planning (0536); Social Research (0344)